2012
DOI: 10.5114/pm.2012.31470
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial conditions of quality of life for women during menopause treated for breast cancer

Abstract: StreszczenieWstęp: Rak piersi jest jednym z najczęściej występujących nowotworów złośliwych wśród kobiet na świecie. Największą liczbę zachorowań odnotowuje się wśród kobiet po 50. roku życia. Choroba nowotworowa stanowi dla kobiety duże obciążenie. Pojawia się uczucie niepewności o swoje zdrowie i dalsze życie, często trudno zaakceptować obraz własnego ciała. Nierzadko obserwuje się również obniżoną samoocenę oraz poczucie wstydu, czemu towarzyszą objawy apatii i zamknięcia się w sobie. Mimo dużego obciążenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Pacian et al (46) found no statistically significant differences between the risk of depression and overall QoL. It has been observed that with older age, depression becomes more common and QoL in the mental and social domains decreases.…”
Section: Discussionmentioning
confidence: 96%
“…Pacian et al (46) found no statistically significant differences between the risk of depression and overall QoL. It has been observed that with older age, depression becomes more common and QoL in the mental and social domains decreases.…”
Section: Discussionmentioning
confidence: 96%
“…Araştırmada elde edilen veriler doğrultusunda HÖGÖ'nin alt boyutlarından biri olan yaşam kalitesi ile meme kanseri evresi arasında istatistiksel olarak anlamlı fark bulunmuştur (p<0.05). Literatür ile bu çalışma benzer sonuçlar göstermekte olup, hastaların genel durumu ve yaşam kalitesi hastalığın evresine bağlı olarak değiştiği Evre I Meme kanserli hastaların ileri evre kanserli hastalara göre yaşam kalitesinin daha yüksek olduğu (Kamińska, 2015) ayrıca genç hastaların yaşlı hastalara göre yaşam kalitesinin daha düşük olduğu (Kamińska, 2015;Pacian, 2012) belirlenmiştir. Bu durum kanserin ilk evrelerinde gösterdiği semptomların ileri evrelere göre daha hafif olması, genç hastaların yaşlılara göre daha sorumluluklarının daha fazla olması yaşam kalitesini olumsuz etkileyebileceği düşünülmektedir.…”
Section: Discussionunclassified
“…Breast cancer is the most common neoplasm in women in Poland, and the second, after lung cancer, cause of cancer-related death, accounting for 22.5% of all cases among cancer patients [1]. The highest number of cases of breast cancer is reported in women over 50 [2][3][4][5][6]. According to the National Cancer Registry, the number of cases of breast cancer in recent years exceeded 16500 and is constantly growing.…”
Section: Introductionmentioning
confidence: 99%